2014
DOI: 10.1126/scitranslmed.3009750
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary transplantation of macrophage progenitors as effective and long-lasting therapy for hereditary pulmonary alveolar proteinosis

Abstract: Hereditary pulmonary alveolar proteinosis (herPAP) is a rare lung disease caused by mutations in the granulocyte-macrophage colony-stimulating factor (GM-CSF) receptor genes, resulting in disturbed alveolar macrophage differentiation, massive alveolar proteinosis, and life-threatening respiratory insufficiency. So far, the only effective treatment for herPAP is repetitive whole-lung lavage, a merely symptomatic and highly invasive procedure. We introduce pulmonary transplantation of macrophage progenitors as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 46 publications
3
100
1
2
Order By: Relevance
“…Following up on recent reports highlighting the self-renewal and repopulating capacity of TRMs as well as their considerable tissue plasticity upon transplantation [9,10], we have recently demonstrated that a single intrapulmonary transplantation of healthy or genetically corrected bone marrow-derived macrophages can substantially improve the disease phenotype of pulmonary alveolar proteinosis in two relevant murine in vivo disease models [11,12]. Although our initial studies used HSPCs derived from murine bone marrow or human cord blood, also iPSC-derived macrophages represent a highly interesting source for cell therapy strategies in diseases related to macrophage dysfunction [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Following up on recent reports highlighting the self-renewal and repopulating capacity of TRMs as well as their considerable tissue plasticity upon transplantation [9,10], we have recently demonstrated that a single intrapulmonary transplantation of healthy or genetically corrected bone marrow-derived macrophages can substantially improve the disease phenotype of pulmonary alveolar proteinosis in two relevant murine in vivo disease models [11,12]. Although our initial studies used HSPCs derived from murine bone marrow or human cord blood, also iPSC-derived macrophages represent a highly interesting source for cell therapy strategies in diseases related to macrophage dysfunction [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Sin embargo, es un tratamiento aun en investigación y del que existe poca evidencia. Una nueva línea de investigación, que evitaría el tratamiento ablativo previo, podría ser el trasplante pulmonar de macrófagos alveolares 46 , que ha mostrado resultados prometedores en modelos murinos y que podría ser una opción de tratamiento en un futuro 47 .…”
Section: Trasplante Alogénico De Precursores Hematopoyéticosunclassified
“…Kürzlich wurde die Transplantation von Makrophagen als vielversprechende Perspektive für die Behandlung der hereditären AP vorgeschlagen [8,15,17].…”
Section: Lungentransplantationunclassified